Analytical Hierarchy Process (AHP) Approach in Selecting the best Retailer: The Case of Novature Sdn Bhd. / Affandi anak Rumpa and Nanang anak William Nai - Rumpa, Affandi; William Nai, Nanang (2014)
Retailer selection is one of the most important tasks for wholesaler. Failure to make the decision about the best retailer will affect the product life span and profitability because not all retailers are best for certain product. Concerning to this problem, retailer selection process needs to be based on decision module that can result the best retailer. Thus, the main objective of this research is to find the best retailer for Novature Sdn Bhd by using AHP module. The typical of AHP module requires three of selection criteria and the possible alternatives. The data about the selection criteria is gathered from unstructured interview with the group of respondent from Novature Sdn Bhd. Then it will evaluate by the competitors and expert group in order to find the top three most preferred criteria. The alternative or retailers had been eliminated based on the selection criteria to identify the top three retailers. From both of this result, the three criteria and alternative are evaluate again in pairwise comparison form. The pairwise comparison from is constructed to evaluating which is the most preferred by the evaluator. The data from pairwise comparison form will be analyse based on the AHP processes to identify the final result about the best retailer out of the top three and supporting by consistency ratio. The recommendations were also given to Novature Sdn Bhd in order to apply AHP with better result and to measure the level of selected retailer success.